GLOBAL LEADERSHIP DEVELOPMENT: THE IMPACT OF INTERNATIONAL HR MANAGEMENT ON CROSS-CULTURAL LEADERSHIP EFFECTIVENESS - Dwiarto, Joko; Perkasa, Didin Hikmah; Saluy, Ahmad Badawi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Globally operating companies face challenges in managing human resources from diverse cultural backgrounds. This paper highlights how the role of International Human Resource Management (IHRM) can support the improvement of cross-cultural leadership effectiveness while strengthening organizational competitiveness at the global level. Based on the analysis of various empirical studies, it is revealed that leadership success is highly dependent on the mastery of cross-cultural competencies, including cultural intelligence, emotional intelligence, and intercultural communication skills. Global leaders who are able to integrate local and international identities, and adopt transformational leadership approaches, tend to be more successful in building synergy and innovation in multicultural teams. Flexible IHRM approaches such as cross-cultural training and international work experience are key factors in shaping leaders with global capacity. The study also emphasizes the need for collaborative, context-relevant and sustainable leadership development strategies, and the importance of integrating inclusive IHRM practices to support organizational performance in a dynamic global work environment.